أثر استراتيجيتي الموقع والمحاولة المتكررة في تحصيل مادة العروض والتفكير التحليلي عند طلبة كليات التربية الأساسية (Journal of the College of Basic Education, 2025)
The researcher adopted the experimental method, selecting a research sample from the University of Kufa, specifically from Najaf Governorate, for the academic year (2023-2024). Second-year students in the Arabic Language Department at the College of Basic Education were chosen as the sample for this study, comprising three groups totaling (121) male and female students. The researcher ensured the equivalence of the three research groups across several variables, formulated behavioral objectives based on the topics to be taught, and prepared an academic achievement test for the subject of prosody, consisting of (40) items, while the analytical thinking test consisted of (30) items. Using statistical methods, the researcher found that students who studied prosody using the positioning and repeated trial strategies outperformed the control group. The researcher concluded that these two strategies, based on constructivist theory, contributed to raising students' academic achievement in prosody. The researcher recommends encouraging teachers to use modern strategies that place the student at the center of the educational process, avoid inductive reasoning and restricting learning freedom, and help students access information independently. She also suggested conducting similar studies in other subjects.